Rivaroxaban With or Without Aspirin in Patients With Heart Failure and Chronic Coronary or Peripheral Artery Disease: The COMPASS Trial. Issue 7 (13th August 2019) - Branch, Kelley R.; Probstfield, Jeffrey L.; Eikelboom, John W.; Bosch, Jackie; Maggioni, Aldo P.; Cheng, Richard K.; Bhatt, Deepak L.; Avezum, Alvaro; Fox, Keith A.A.; Connolly, Stuart J.; Shestakovska, Olga; Yusuf, Salim
Abstract : Background: Patients with chronic coronary artery disease or peripheral artery disease and history of heart failure (HF) are at high risk for major adverse cardiovascular events. We explored the effects of rivaroxaban with or without aspirin in these patients. Methods: The COMPASS trial (Cardiovascular Outcomes for People Using Anticoagulation Strategies) randomized 27 395 participants with chronic coronary artery disease or peripheral artery disease to rivaroxaban 2.5 mg twice daily plus aspirin 100 mg daily, rivaroxaban 5 mg twice daily alone, or aspirin 100 mg alone. Patients with New York Heart Association functional class III or IV HF or left ventricular ejection fraction (EF) <30% were excluded. The primary major adverse cardiovascular events outcome comprised cardiovascular death, stroke, or myocardial infarction, and the primary safety outcome was major bleeding using modified International Society of Thrombosis and Haemostasis criteria. Investigators recorded a history of HF and EF at baseline, if available. We examined the effects of rivaroxaban on major adverse cardiovascular events and major bleeding in patients with or without a history of HF and an EF <40% or ≥40% at baseline. Results: Of the 5902 participants (22%) with a history of HF, 4971 (84%) had EF recorded at baseline, and 12% had EF <40%. Rivaroxaban and aspirin had similar relative reduction in major adverse cardiovascular events compared with aspirin in participants with HF (5.5% versus 7.9%; hazard ratio [HR], 0.68; 95% CI, 0.53–0.86) and those without HF (3.8% versus 4.7%; HR, 0.79; 95% CI, 0.68–0.93; P for interaction 0.28) but larger absolute risk reduction in those with HF (HF absolute risk reduction 2.4%, number needed to treat=42; no HF absolute risk reduction 1.0%, number needed to treat=103). The primary major adverse cardiovascular events outcome was not statistically different between those with EF <40% (HR, 0.88; 95% CI, 0.55–1.42) and ≥40% (HR, 0.81; 95% CI, 0.67–0.98; P for interaction 0.36). The excess hazard for major bleeding was not different in participants with HF (2.5% versus 1.8%; HR, 1.36; 95% CI, 0.88–2.09) than in those without HF (3.3% versus 1.9%; HR, 1.79; 95% CI, 1.45–2.21; P for interaction 0.26). There were no significant differences in the primary outcomes with rivaroxaban alone. Conclusions: In patients with chronic coronary artery disease or peripheral artery disease and a history of mild or moderate HF, combination rivaroxaban and aspirin compared with aspirin alone produces similar relative but larger absolute benefits than in those without HF. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01776424. Abstract : Supplemental Digital Content is available in the text.